Integrasi Metode OMAX, AHP, dan HIRA dalam Evaluasi Produktivitas dan Risiko Operasional pada UMKM Tahu - Juli Andry; Nazaruddin; Nur, Muhammad; Suherman; Taslim, Rika (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2025)
Productivity is an important indicator in increasing the efficiency and competitiveness of MSMEs, especially in the tofu industry which faces the challenge of production costs and dependence on imported raw materials. This study aims to measure and increase the productivity of the Pak Budi Tofu Factory through the integration of three methods of Objective Matrix (OMAX), Analytical Hierarchy Process (AHP), and Hazard Identification and Risk Assessment (HIRA). The OMAX method is used to assess productivity based on four main ratios, AHP to determine the priority weight of causative factors, and HIRA to identify internal and external risks that affect productivity. The results show fluctuations in the productivity index during 2023, with the highest value in April (176.82%) and lowest in February (-75.69%). AHP showed raw material efficiency as the dominant factor (weight 0.428), while HIRA revealed the main risks in the form of high worker absenteeism, production machine disruptions, and dependence on imported soybeans. This study concludes that the integration of the three methods can provide a comprehensive productivity analysis and support data-driven decision-making in the MSME sector.